Long noncoding RNA HOTAIRM1 promotes myeloid-derived suppressor cell expansion and suppressive functions through up-regulating HOXA1 expression during latent HIV infection. (1st December 2020) - Zhang, Jinyu; Thakuri, Bal Krishna Chand; Zhao, Juan; Nguyen, Lam N.; Nguyen, Lam N.T.; Cao, Dechao; Dang, Xindi; Khanal, Sushant; Schank, Madison; Lu, Zeyuan; Wu, Xiao Y.; Morrison, Zheng D.; et al.
Abstract : Objective: Myeloid-derived suppressor cells (MDSCs) contribute to HIV progression by impairing antiviral immunity; however, the mechanisms responsible for MDSC development during HIV infection are incompletely understood. HOX antisense intergenic RNA myeloid 1 (HOTAIRM1) is a long noncoding RNA (lncRNA) that plays a pivotal role in regulating myeloid cell development via targeting HOXA1. The role of HOTAIRM1--HOXA1 in the differentiation and functions of MDSCs during HIV infection remains unclear. Methods: In this study, we measured MDSC induction and suppressive functions by flow cytometry, RT-PCR, and co-culture experiments using CD33 + myeloid cells derived from people living with HIV (PLHIV) on antiretroviral therapy (ART). We also manipulated the HOTAIRM1--HOXA1 axis in myeloid cells using knockdown and overexpression approaches. Results: We demonstrate that HOTAIRM1 and HOXA1 expressions are reciprocally upregulated and are responsible for increased levels of immunosuppressive molecules, such as arginase 1 (Arg1), inducible nitric oxide synthase (iNOS), signal transducer and activator of transcription 3 (STAT3), and reactive oxygen species (ROS), in CD33 + myeloid cells derived from PLHIV on ART. We found that overexpression of HOTAIRM1 or HOXA1 in CD33 + cells isolated from healthy individuals promoted the differentiation and suppressive functions of MDSCs, whereas silencing of HOTAIRM1 or HOXA1 expression in MDSCs derived from PLHIV significantly inhibited the frequency of MDSCs and expressions of the immunosuppressive molecules and reduced their immunosuppressive effects on T cells. Conclusion: These results indicate that the HOTAIRM1--HOXA1 axis enhances differentiation and suppressive functions of MDSCs and could be a potential therapeutic target for immunomodulation during latent HIV infection.